Polygonal faulting and seal integrity in the Bonaparte Basin, Australia. (February 2015) - Seebeck, Hannu; Tenthorey, Eric; Consoli, Chris; Nicol, Andrew
Abstract: Polygonal fault systems are observed in over 100 sedimentary basins worldwide where they are confined to fine-grained strata and have the potential to impact on seal integrity for CO2 storage and hydrocarbon reservoirs. 3D seismic reflection and well data have been used to characterise a layer-bound polygonal fault system and gas chimneys in the Bathurst Island Group regional seal, Petrel Sub-basin, offshore NW Australia. Segmented fault arrays extend through the entire faulted interval which contains at least 10 tiers of polygonal faults each spanning ∼4 Myrs of sediment deposition. Polygonal fault densities and intersections reach a maximum at 1000–1100 ms TWT and in some cases extend into the Sandpiper Sandstone reservoir at >1200–1300 ms TWT. Down-dip displacement profiles are symmetrical and increase progressively across tier boundaries towards maxima of ∼25–47 ms between 600 and 1100 ms. These systematic displacement variations are similar to those of tectonic faults and suggest that fault segments in different tiers develop synchronously as kinematically coherent arrays. Three-dimensional imaging of the polygonal fault system indicates that throughout the Bathurst Island Group the fault network is well connected vertically and horizontally. Polygonal faulting may locally promote gas flow through the seal to the seabed suggesting that, where faulted, the Bathurst Island Group may not be an effective seal for CO2 storage in the study area. Highlights: High resolution mapping performed on a polygonal fault network in Bonaparte Basin. Polygonal fault network is tiered with tiers being traceable across basin. Natural seepage indicators suggest gas migration on geologic time scales. High degree of fault connectivity a potential risk for caprock integrity.